Pengaruh Penerapan Budaya Organisasi dan Efektivitas Pengendalian Internal terhadap Kualitas Sistem Informasi Akuntansi Manajemen - Maulina Fauziah; Nurleli (UNISBA Press, 2024)
Abstract. Management Accounting Information System (SIAM) is an information system that produces output using input and various processes required to meet management objectives. In general, it can be said that the purpose of a management accounting information system is to provide information to management that enables them to carry out their functions from planning to decision making. So it can be said that the quality of a management accounting information system is the ability of a management accounting information system to produce the information needed by management to enable them to carry out their functions from planning to decision making. Many factors influence the quality of management accounting information systems, including the implementation of organizational culture and the effectiveness of internal control. The aim of this research is to determine how much influence the application of organizational culture and the effectiveness of internal control affects the quality of the management accounting information system in the UMKM Shoe Sector in Cibaduyut, Bandung City. The research method used is verification with a quantitative approach. The data collection technique used was a questionnaire with 40 MSME respondents in the Cibaduyut Shoe Sector, Bandung City. The sampling technique in this research is non-probability sampling with convenience sampling type. The research results show that the implementation of organizational culture has no effect on the quality of the management accounting information system, and the effectiveness of internal control has an effect on the quality of the management accounting information system. Abstrak. Sistem Informasi Akuntansi Manajemen (SIAM) adalah sistem informasi yang menghasilkan output dengan menggunakan input dan berbagai proses yang diperlukan untuk memenuhi tujuan manajemen. Kualitas sistem informasi akuntansi manajemen adalah kemampuan sistem informasi akuntansi manajemen yang menghasilkan informasi yang dibutuhkan manajemen yang memungkinkan mereka untuk menjalankan fungsinya mulai dari perencanaan hingga pembuatan keputusan. Banyak factor yang mempengaruhi kualitas system informasi akuntansi manajemen diantaranya penerapan budaya organisasi dan efektivitas pengendalian internal. Tujuan penelitian ini adalah untuk mengetahui seberapa besar pengaruh penerapan budaya organisasi dan efektivitas pengendalian internal mempengaruhi kualitas system informasi akuntansi manajemen di UMKM Sektor Sepatu Cibaduyut Kota Bandung. Metode penelitian yang digunakan adalah verifikatif dengan pendekatan kuantitatif. Adapun teknik pengumpulan data yang digunakan adalah kuesioner dengan 40 responden UMKM Sektor Sepatu Cibaduyut Kota Bandung. Teknik pengambilan sampel pada penelitian ini adalah non probability sampling dengan jenis convenience sampling. Hasil penelitian menunjukkan bahwa penerapan budaya organisasi tidak berpengaruh terhadap kualitas sistem informasi akuntansi manajemen, dan efektivitas pengendalian internal berpengaruh terhadap kualitas sistem informasi akuntansi manajemen.